2004
DOI: 10.1369/jhc.3a6227.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junctional Communication and Connexin43 Expression in Relation to Apoptotic Cell Death and Survival of Granulosa Cells

Abstract: S U M M A R YOvarian follicular atresia in all vertebrates is mediated via apoptosis that is initiated in the granulosa cell layer. Here we investigated the relation between connexin expression, cell coupling, and apoptosis in avian granulosa cells. Results from qualitative and quantitative immunocytochemical analysis and Western blotting of connexin43 (Cx43) and electron microscopic observations of gap junctions were compared with functional data on gap junctional coupling obtained by fluorescence recovery af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 58 publications
6
40
0
Order By: Relevance
“…Treatment of wellcoupled GFSHR-17 granulosa cells with gap junction uncouplers has been reported to promote apoptosis (Ngezahayo et al, 2005). However, in primary granulosa cells, the induction of apoptosis was actually associated with increased cell coupling, and upon gap junction blockade, apoptosis was inhibited (Krysko et al, 2004). We note that a specific role for Cx43␣1 in apoptosis has been suggested in a number of other studies (Albright et al, 2001;Furlan et al, 2001;Nakase et al, 2004;Yasui et al, 2000).…”
Section: Research Articlementioning
confidence: 49%
“…Treatment of wellcoupled GFSHR-17 granulosa cells with gap junction uncouplers has been reported to promote apoptosis (Ngezahayo et al, 2005). However, in primary granulosa cells, the induction of apoptosis was actually associated with increased cell coupling, and upon gap junction blockade, apoptosis was inhibited (Krysko et al, 2004). We note that a specific role for Cx43␣1 in apoptosis has been suggested in a number of other studies (Albright et al, 2001;Furlan et al, 2001;Nakase et al, 2004;Yasui et al, 2000).…”
Section: Research Articlementioning
confidence: 49%
“…Direct intercellular communication by gap junctions is mediated primarily by passive diffusion of small hydrophilic molecules, such as glucose, glutamate, glutathione, cAMP, ATP, inositol triphosphate (IP 3 ), calcium, potassium, and sodium (48,54,74). Gap junction proteins (and Cx43 in particular) can regulate cell death and survival, cell growth, and cell differentiation through several mechanisms, which are either dependent or independent of channel activity (79)(80)(81)(82)(83). Cx43 has been localized not only to gap junctions but also to intracellular sites, including mitochondria (48,76,79,80,84).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that changes in GJIC can influence cell survival or apoptosis. [28][29][30] In rat ventricular myocytes, reduced Cx43 expression resulted in increased apoptosis. 31 Similar effects were found in mammary epithelial cells with lower connexin 26 expression.…”
Section: Introductionmentioning
confidence: 99%